Faktor Yang Mempengaruhi Produksi Gilingan Padi Di Kecamatan Lima Kaum Kabupaten Tanah Datar - febria rahim (AL-ITTIFAQ: Jurnal Ekonomi Syariah, 2021)
The purpose of this study was to examine the effect of raw materials, fuel and labor on the production of rice mills in Lima Kaum District, Tanah Datar Regency. This research is a field research with a quantitative approach. The data source that the writer uses is the primary data source by using a questionnaire distribution technique. The data analysis technique that the author uses is the validity test, reliability test, classical assumption test, multiple linear regression method and hypothesis testing. The results of this study indicate that the raw materials partially have a positive and significant effect on the production of rice mills, with a significant value of 0.000 <0.05. Fuel partially has a positive and significant effect on the production of rice mills, with a significant value of 0.000 <0.05. Labor partially has a positive and significant influence on the production of rice mills, with a significant value of 0.000 <0.05. Raw materials, fuel and labor simultaneously have a significant effect on the production of rice mills, with a significant value of 0.000 < 0.05.